Parental Parenting Patterns and Early Childhood Social Emotional Development: Pengaruh Penggunaan Aplikasi Grammarly terhadap Prestasi Menulis Teks Narasi Siswa Sekolah Menengah Atas - Agustin Deliya Sari; Agus Salim (Academia Open, 2025)
General Background Early childhood represents a critical period for the formation of social and emotional competencies that shape children’s behavior and future learning readiness. Specific Background Family environments and parenting practices play a central role in guiding children’s emotional regulation, cooperation, and social interaction. Knowledge Gap Despite numerous discussions on early childhood development, contextual evidence describing how different parenting patterns relate to children’s social emotional behavior in local settings remains limited. Aims This study aims to analyze the relationship between parental parenting patterns and the social emotional development of early childhood learners. Results Findings indicate that democratic and supportive parenting is associated with positive behaviors such as confidence, empathy, and cooperation, while inconsistent or permissive approaches correspond with lower emotional control and social difficulties. Novelty The study provides field-based qualitative insights that integrate observations, interviews, and documentation to portray parenting practices within a specific educational community. Implications The results suggest that strengthening parent involvement and informed caregiving practices can support balanced social emotional growth in early childhood education settings. Keywords: Parenting Patterns, Social Emotional Development, Early Childhood Education, Family Environment, Qualitative Study Key Findings Highlights: Supportive caregiving linked with cooperative and confident behaviors Inconsistent supervision associated with weaker emotional regulation Home practices aligned with classroom social readiness